Efficacy of half-back play in rugby and the impact of substitutions - Smyth, G.; Hughes, M. (Journal of Human Sport & Exercise, 2016)
An exploratory method of quantifying the impact of individual players in rugby union was developed and applied to both half-back positions in 2015 Rugby World Cup matches, with a view to assessing the impact of their substitutions. It was hoped to extend this method to all positions. Instances where the starting half-back and the replacement played more than 20 minutes of the game were analysed. A match impact scoring system was devised using the questionnaire responses of an expert group of professional rugby analysts and experienced international coaches. The scoring system weighted each game action in a positive or negative manner according to the impact on team performance. The final match impact score for each player was divided by the number of seconds the team had in possession. Sample data from the study would indicate that the starting scrum-half had a higher mean impact score than the replacement scrum-half (9.64 +/- 3.94 and 8.74 +/- 4.2 respectively). The replacement out-half appeared to have a greater game impact than the starting out-half (7.49 +/- 3.66 and 5.11 +/- 4.30). An Intra-positional comparison of out-half and scrum-half positions showed that the out-half (6.30 +/- 3.91) has lower mean game impact than scrum half (9.18 +/- 4.38). The high standard deviation figures indicate that the impact of extraneous variables, such as evolving match score and weather conditions present many challenges to players. The findings of this study would indicate that further research should examine the impact of substitutions in all positions in the team, with a view to forming a performance profile of replacement players and to quantify their contribution to match outcome.